Front Matter (Journal of the Assembly for Expanded Perspectives on Learning, 1999)
Editor's Message Zen students, Charlotte Joko Beck tells us, have a job to do, "a very important job: to bring . . . life out of dreamland and into the real and immense reality that it is" (12). The goal and the way to the goal are the same: mindfulness, a return to the clear experience of the present moment, within which the artificial dualism separating self and object dissolves. To be mindful is to be aware, The American Heritage Dictionary says, to hold in the fullness of mind rather than to be destitute of mind or consciousness. Mindfulness is the key to human interaction, to memory, to learning. Captured by our awareness of the moment, we listen and attend. "Mind me," we tell our children. "Hear me," our children respond. "Pay attention," we tell our students; "pay attention," our students respond. Each request and command weaves out of and returns to mindfulness, the heart of living and teaching. In a variety of ways, each essay in this our fifth edition of the Journal of the Assembly for Expanded Perspectives on Learning addresses the quality and importance of teaching in the fullness of the moment. David Bleich in "Learning from Everyone," opens this issue with a plea that we mind or attend language in the moment of its performance, as it lives, rather than to the emptiness of a textual form. "It is easier to teach language when it is living within you," he points out, adding that "[i]t is more interesting if we pay attention to how things are said and try to understand why they are said in just that way." Lisa Tyler's "Narratives of Pain" emphasizes the psychological and physiological value gained by attending to trauma through writing. By offering our students the option of writing about painful events in their lives, we invite them to hold those events within the fullness of mind and possibly initiate the healing process. In "Writer Motivation: Beyond the Intrinsic/Extrinsic Dichotomy," Bradford A. Barry highlights the need for mindfulness in our students' writing tasks, the need for our students "to be immersed in writing tasks that teach students about themselves and the world around them." He offers a theory of rhetorically-based intrinsic motivation called rhetrinsic introphy that fuses self-determination and flow theories with rhetorical concerns. Kia Jane Richmond in "The Ethics of Empathy: Making Connections in the Writing Classroom" reminds us of the need for empathy in the writing classroom regardless of the assignments or the theories from which we work. She defines empathy as a dialectic between cognition and emotion, one that requires mindful listening to our students rather than the superficial mindless response that solves the students' problems before they are even defined. Catherine L. Hobbs attends to the demands of the information age, offering the "architectonic arts" of Neapolitan philosopher Giambattista Vico as a means to structure our attention in a world that floods us with information. In "The Architectonics of Information," Hobbs points out the crisis of attention caused by the information age and suggests that Vico's structuring arts based on metaphor and imagery can serve as a productive way to transform ourselves into intelligent agents, mindful of the barrage of information around us and the ways in which we can control it. Finally, Susan Schiller addresses mindfulness explicitly in a classroom incorporating meditation techniques that increase students' spiritual connection to self and world. In "Spirituality in Pedagogy: A Field of Possibilities," Schiller describes a course designed to enhance her students' awareness of the moment through meditation, a process that stimulates growth in the comprehension of subject matter. Such pedagogy, she writes, requires that teacher and students be joined in a like commitment to the possibilities of heightened listening through meditation. Mindfulness connects us to the moment, to ourselves, and to the world. "The first great discovery of mindfulness meditation," Francisco J. Varela, Evan Thompson, and Eleanor Rosch write in The Embodied Mind, "tends to be not some encompassing insight into the nature of mind but the piercing realization of just how disconnected humans normally are from their very experience" (25). The range of essays within this volume highlights the ways in which we all can better attend to the fullness of the moment and by so doing reconnect on myriad levels with the world around and within us. As teachers and as students, "we have to pay attention to this very moment, the totality of what is happening right now (Beck 10). Works Cited Beck, Charlotte Joko. Everyday Zen: Love and Work. San Francisco: HarperCollins, 1989. Varela, Francisco J., Evan Thompson, and Eleanor Rosch. The Embodied Mind: Cognitive Science and Human Experience. Cambridge, MA: MIT Press, 1996.